SCIRPOPHAGA EXCERPTALIS WALKER INFESTATION IN RELATION TO ITS NATURAL PARASITOIDS AND SUGARCANE CULTIVARS IN EASTERN UTTAR PRADESH - TANMAR, R.K.; VARMA, ASHOK (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
The sugarcane top borer. Scirporaea etcerptatis Wlk infestation in relation to its parasitoids and cultivars were studied in eastern Uttar Pradesh during 1987 to 1989. Of the two egg parasitoids and seven larval parasitoids recorded in the region, the most prevalent were Telenomus digmus Gahan and Isotima javensis Row, Rhaconotus scirpophagae Wik and Glamorpha (Stenobracon) nicevillei Bingham as egg and larval parasitoids, respectively. The cumulative passation by prevalent parasitoids could not suppress S. excerptalis population buildup through successive seasons. Among the locally grown of the commercial cultivars screened, BO 91 was less infested by S. excerpts and was found to be tolerant under field conditions as compared with cultivars, CoS 7918, Co 1148, CoJ 64 and CoS 770. Due to ineffectiveness of the existing natural enemy complex and non availability of multiplication techise of the host top borer and its parasitoids, growing tolerant varieties appeared to be only feasible strates the management of S. excerptalis in endemic area of the region.